Large-area plasmon enhanced two-dimensional MoS2. Issue 42 (18th October 2017) - Lee, Min-Gon; Yoo, SeokJae; Kim, TaeHyung; Park, Q-Han
Abstract : Two-dimensional transition metal chalcogenides (2D TMDCs) show photoluminescence (PL) enhancement as a result of the coupling between plasmon resonance of gold nanoparticles and direct band-gap transitions of 2D TMDCs. Abstract : Two-dimensional transition metal chalcogenides (2D TMDCs) show photoluminescence (PL) as a result of direct band-gap transitions at visible wavelengths. Although 2D TMDCs have been considered for use in next-generation optoelectronics, practical applications are restricted by their low absorption and emission efficiency. To overcome these limitations using plasmonic local field enhancement, we propose the integration of gold nanoparticles with 2D TMDCs over a centimeter-scale area. Using self-assembled gold nanoshell monolayers, we produce a 10-fold increase in the PL of 2D TMDCs. We expect our method to provide a means for the large-area, low-cost fabrication of plasmon-enhanced 2D TMDCs for optoelectronic applications.